Integration of Knowledge Management and E- Learning Technologies in Academic Institutions - Oloruntoyin, Sefiu Taiwo (Universitas Islam Negeri Alauddin Makassar, 2020)
This work investigates the integration of e-Learning systems and knowledge management technology to improve, capture, organize and deliver large amounts of knowledge. First, a model is proposed for the phases of knowledge management. The model is then enhanced with concepts and technology from e-Learning. The model is then used to illustrate real world scenarios that add increasing amounts of knowledge management to an e-Learning environment. The system, AMID promises high interactivity, efficiency and effectiveness of integration of knowledge management and e-learning. In addition, the developed system will enhance technical learning process.